2005
DOI: 10.1371/journal.pmed.0020160
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation and Cardiovascular Disease Risk Factors: Results from the Third National Health and Nutrition Examination Survey

Abstract: BackgroundCigarette smoking is a major risk factor for the development and progression of cardiovascular disease. While smoking is associated with increased levels of inflammatory markers and accelerated atherosclerosis, few studies have examined the impact of smoking cessation on levels of inflammatory markers. The degree and rate at which inflammation subsides after smoking cessation are uncertain. It also remains unclear as to whether traditional risk factors can adequately explain the observed decline in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 57 publications
5
130
0
7
Order By: Relevance
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
“…These studies have generally shown higher levels of hsCRP among current and former smokers compared with nonsmokers5, 6, 9, 10, 12, 13, 14, 15 and decreased levels after smoking cessation, albeit slower than systolic blood pressure and total cholesterol and LDL‐C 8, 11, 12. Calculating the probability of CAC onset following smoking exposure in the Heinz Nixdorf Recall study also demonstrated that onset of CAC was expedited by 10 years among current smokers and 5 years among former smokers compared with never smokers 16.…”
Section: Discussionmentioning
confidence: 99%
“…18,[47][48][49][50] The association of smoking and inflammation is also supported by epidemiologic studies which demonstrated a positive association of cigarettes per day with hsCRP, white blood cell count, and fibrinogen in univariate analyses. 25 Data from this study indicates that smoking intensity is independently associated with inflammation in a dose dependent manner and that hsCRP is the most sensitive biomarker of this association as compared to IL-2, IL-6, and TNF-alpha.…”
Section: Inflammationmentioning
confidence: 68%
“…Since cerebrovascular infarction is the key pathophysiological mechanism for vascular dementia, the risk factors of cerebrovascular diseases, which include smoking,43, 44 are also considered to be risk factors of vascular dementia. As smoking cessation reduces the risk of cardiovascular disease due to decreased inflammatory markers and oxidative stress45, 46, 47 upon smoking cessation, similar mechanisms may contribute to the decreased risk of vascular dementia.…”
Section: Discussionmentioning
confidence: 99%